2010
DOI: 10.1038/ijo.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute dietary restriction on gut motor, hormone and energy intake responses to duodenal fat in obese men

Abstract: Background: Previous patterns of energy intake influence gastrointestinal function and appetite, probably reflecting changes in small-intestinal nutrient-mediated feedback. Obese individuals consume more fat and may be less sensitive to its gastrointestinal and appetite-suppressant effects than lean individuals. Objective: To evaluate the hypothesis that, in obese individuals, the effects of duodenal fat on gastrointestinal motor and hormone function, and appetite would be enhanced by a short period on a very-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
2
20
2
1
Order By: Relevance
“…On the other hand, it is increased after 4 weeks on a low-fat diet ( 20 ). Similarly, acute dietary restriction in obese subjects enhances gastrointestinal sensitivity to fat, which is associated with an increased effect of fat on satiation ( 45 ). Although we demonstrated the existence of a relationship between fat perception sensitivity and genotype, our study was not able to determine whether oral fat perception sensitivity affects fat intake or body weight.…”
Section: Infl Uence Of Orlistat On Oleic Acid and Triolein Detection contrasting
confidence: 57%
“…On the other hand, it is increased after 4 weeks on a low-fat diet ( 20 ). Similarly, acute dietary restriction in obese subjects enhances gastrointestinal sensitivity to fat, which is associated with an increased effect of fat on satiation ( 45 ). Although we demonstrated the existence of a relationship between fat perception sensitivity and genotype, our study was not able to determine whether oral fat perception sensitivity affects fat intake or body weight.…”
Section: Infl Uence Of Orlistat On Oleic Acid and Triolein Detection contrasting
confidence: 57%
“…A 30% energy restriction is also concordant with many weight-loss diets. Although fasting ghrelin and hunger ratings were elevated after the dietary restriction, the magnitude of their suppression by intraduodenal lipid was enhanced, and energy intake was markedly reduced (10). In the current study, we observed increased peptide YY and reduced cholecystokinin in response to intraduodenal lipid and an increase in the desire to eat on day 5; however, there were no differences in BPP, IPPWs, antral and duodenal pressures, ghrelin, or energy intakes.…”
Section: Discussioncontrasting
confidence: 62%
“…A silicone-rubber manometry catheter that incorporated 16 channels (Dentsleeve International Ltd) was inserted through an anesthetized nostril into the stomach and allowed to pass into the duodenum by peristalsis (22). Six side holes (channels 1-6) were positioned in the antrum, a 4.5-cm pyloric sleeve sensor (channel 7), with 2 channels present on the back of the sleeve (channels 8 and 9), was positioned across the pylorus, and 7 side holes (channels [10][11][12][13][14][15][16] were positioned in the duodenum. An additional channel, 11.75 cm distal to the pylorus, was used for the intraduodenal infusion.…”
Section: Study Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, if these signals change in the obese humans in response to energy-restricted weight loss, a collective signal favoring hunger over satiety/satiation is observed (Table 1). However, detection of this adaptive response is much less consistent than that of circulating adipose signals and nutrients, as they may be dependent on the presence of a negative energy balance (2,30,42,71,133), the amount of weight loss (71), the amount of physical activity (121), the specific derivative of the hormone measured [peptide YY(PYY) vs. PYY3-36; total vs. acetylated ghrelin] (18) or the type of macronutrient restricted in the diet (71,95). Even under the same conditions of weight loss and maintenance, there is a wide variability in individual responses with respect to these adaptations in hunger and satiety signals (18).…”
Section: The Gut: Sensing the Prandial Statementioning
confidence: 99%